The hospitable institution? Researching participation in a gallery youth collective - Kill, Cassandra M B (2024)
In recent years, the youth collective has become a widespread feature in UK contemporary art galleries, based on sustained, regular participation, which often espouses the aim of positioning young people as institutional insiders. Within the cultural sector, participation in the gallery youth collective is often claimed to render elite institutions more inclusive, democratic, and porous, and to benefit young people professionally, personally, and politically.